2013
DOI: 10.2215/cjn.06960712
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Changes Associated with Aldosterone Breakthrough after Angiotensin II Receptor Blockade in Patients with Type 2 Diabetes with Overt Nephropathy

Abstract: SummaryBackground and objectives Inhibition of the renin-angiotensin-aldosterone system decreases proteinuria and slows estimated GFR decline in patients with type 2 diabetes mellitus with overt nephropathy. Serum aldosterone levels may increase during renin-angiotensin-aldosterone system blockade. The determinants and consequences of this aldosterone breakthrough remain unknown.Design, setting, participants, & measurements This study examined the incidence, determinants, and changes associated with aldosteron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 31 publications
(23 reference statements)
0
29
0
Order By: Relevance
“…In 10-50% of patients' circulating aldosterone concentrations return to pre-treatment levels (a phenomenon termed 'aldosterone breakthrough'). 45 There are reports that patients who demonstrate aldosterone breakthrough have a worse prognosis than those who do not. 45 It has been suggested that the use of MRA in this context would be beneficial, especially in the context of renal impairment, and there are many animal and human studies to support this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 10-50% of patients' circulating aldosterone concentrations return to pre-treatment levels (a phenomenon termed 'aldosterone breakthrough'). 45 There are reports that patients who demonstrate aldosterone breakthrough have a worse prognosis than those who do not. 45 It has been suggested that the use of MRA in this context would be beneficial, especially in the context of renal impairment, and there are many animal and human studies to support this.…”
Section: Discussionmentioning
confidence: 99%
“…45 There are reports that patients who demonstrate aldosterone breakthrough have a worse prognosis than those who do not. 45 It has been suggested that the use of MRA in this context would be beneficial, especially in the context of renal impairment, and there are many animal and human studies to support this. 2 A further important and not unexpected finding of this analysis was that there was a significant increase in serum potassium concentrations and a significant increase in the risk of hyperkalemia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Hosoya et al [15] have recently demonstrated that the expression of the aldosterone-producing enzyme CYP11B2 in the adipose tissue of 5/6-nephrectomized rats is upregulated, leading to increased tissue aldosterone content. Finally, aldosterone breakthrough phenomenon (i.e., an elevation in plasma aldosterone levels 3-6 months after the administration of RAS inhibitors) could be a possible mechanism for aldosterone dysregulation [32,33]. Taken together, these mechanisms may act in concert to enhance aldosterone activity in CKD.…”
Section: Aldosterone In Ckdmentioning
confidence: 99%
“…Furthermore, the expression of CYP11B2, an aldosterone-producing enzyme, in the adipose tissue of 5/6-nephrectomized rats is upregulated, resulting in increased tissue aldosterone content [15]. Finally, the continued use of ACE inhibitors or ARB may cause paradoxical increases in plasma aldosterone concentrations through aldosterone breakthrough phenomenon [32,33]. These mechanisms would act in concert to elevate plasma aldosterone concentrations as renal function declines.…”
Section: Non-epithelial Action Of Aldosteronementioning
confidence: 99%
“…Moranne et al found that initial plasma potassium and aldosterone concentrations, as well as higher decreases in sodium intake, systolic BP (SBP), and estimated GFR (eGFR) from baseline to 1 year were factors that influence plasma aldosterone level. 14 The aim of the present study was to determine whether those parameters mentioned above, including initial plasma potassium and aldosterone concentration, higher decreases in sodium intake, SBP, and eGFR from baseline to 1 year, as well as the transtubular K gradient (TTKG) (an index of potassium secretion from the collecting ducts), can predict the clinical effects of Ep add-on therapy on BP and proteinuria in patients already taking ACEis or ARBs.…”
Section: Introductionmentioning
confidence: 99%